Pengaruh Kepadatan Ayam Didalam Kandang Terhadap Konsumsi Pakan, Pertambahan Bobot Badan, dan Konversi Pakan Pada Ayam Arab (Gallus turcicus) Jantan Periode Grower - Usman Rozali; Muharlien Muharlien; Heni Prayogi (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
The purpose on this research was to find out the effect of chickendensity in the cageonfeed intake, body weight gain and feed conversion of Arabic chicken for grower phase. The material used were 50 birds of Arabic chicken attheage of 60 days with average initial body weight of 743.5 ± 67.28. The variables observed in this study were the feed intake, body weight gain and feed conversion. The method used was experiment using Completely Randomized Design consist of 4 treatments and 5 replications. The obtained data were analyzed by using ANOVA followed by Duncan’s Multiple Range Test (DMRT).The results of this study showed that there was no significant different between house density on body weight gain and feed conversion, but there was avery significantly different (P<0.01) on feed intake. Based on this study, it can be concluded that the better chickendensity in the cage for Arabic chicken at grower phase uses 4 birds / 1200 cm2 birds/m2, because it performed better body weight gain and feed conversion. So, it is suggested that the farmer would likely to use chickendensity in the cage at 4 birds / 1200 cm2for Arabic chicken of grower phase.